A brief atlas of the human body - Hutchinson, Matt.; Mallatt, John.; Marieb, Elaine. N. (India : Pearson Education, 2003)
A Brief Atlas of the Human Body evolved from a joint inspiration of Elaine N. Marieb and Benjamin Cummings Publisher Daryl Fox: The Atlas of the Human Skeleton, which was packaged with Human Anatomy & Physiology, fifth edition, and Human Anatomy, third edition, upon their publication in 2000. The full-color views of the human skeleton in that atlas provided students with a degree of clarity and scale that could never be achieved within a textbook alone. Building upon our original vision, this new atlas features 47 soft tissue images, in addition to the 104 bone images featured in the Atlas of the Human Skeleton. - Preface.
Keywords: Human anatomy -- Atlases; Anatomy; Human Body